벌포금속을 삽입한 밀집형 열교환기의 최적 설계 - 이대영; 진재식; 강병하 (대한설비공학회, 2001)
The optimum design of a heat exchanger with porous media insertion is studied in this paper. It is considered that the aluminum foam metal is inserted in a flat plate channel and air flows through it. The influence of the microstructure of the foam metal on the pressure drop and heat transfer is investigated utilizing previous analytical results and existing correlation equations. Design parameters are identified as the unit-cell size and the ligament thickness of the porous medium, and their effects are examined. The results show that there exists optimum microstructure of the porous media maximizing heat transfer with a constant pressure drop. When the increase in the pressure drop is within a practically acceptable range, the increase in the heat transfer is dominated by the increase in the heat transfer area due to the porous medium insertion. Consequently, among the porous media with a constant pressure drop, the heat transfer is maximized with a microstructure with maximum specific surface area.